Peran Konseling Logo dalam Meningkatkan Hidup Bermakna (Meaning Life) pada Wanita Single Mother Di Bandung - endah nawangsih; Dwi Edriyanti (Universitas Islam Bandung, 2011)
The Purpose of this study is to increase understanding of the meaning of life at single mother women. This study uses a cognitive approach. Through this cognitive approach obtained a negative self-image of how the subject thinks of himself. This negative self-assessment will be changed in the intervention, i.e by growing new understanding (insight) on the subjects themselves through restructuring the way of their thinking. This is being the basis of considerations that a change in the pattern of thinking will be followed by changes in behavior. The results obtained in this study carried out, it is understood in the sense that if the subjects of this study demonstrated a new perspective in assessing themselves, as well as the existence of self-conciousness, so that they have wrong perception about meanings of life, then at this stage means they have insight experienced. When insight is achieved, the subjects were invited to organize the necessary steps to achieve meaningful life. Subjects will get a new self-image, which they think themselves more valuable, and meaningful. In other words, the steps can be taken to find meaning in life is to create positive thinking on the subjects themselves.